Bridging the Transient Intraluminal Stroke Preclinical Model to Clinical Practice: From Improved Surgical Procedures to a Workflow of Functional Tests - Pinto, Raquel; Magalhães, Ana; Sousa, Mafalda; Melo, Lúcia; Lobo, Andrea; Barros, Pedro; Gomes, João R. (Frontiers in Neurology, 2022)
Acute ischemic stroke (AIS) remains a leading cause of mortality/disability, despite significant advances in therapy (endovascular thrombectomy). The failure in developing novel effective therapies is associated with unsuccessful translation from preclinical studies into clinical practice, associated to inconsistent and highly variable infarct areas and the lack of relevant post-stroke functional evaluation in preclinical research. To outreach these limitations, we optimized the intraluminal transient middle-cerebral-occlusion, a widely used mouse stroke model, in two key parameters- the selection of appropriate occlusion filaments and the time of occlusion- that show significant variation in the literature. We demonstrate that commercially available filaments with short coating length (1-2mm), together with 45-min occlusion, results ina consistent affected brain region, similar to what is observed in most AIS patients. Importantly, a dedicated post-stroke care protocol, based on clinical practice applied to stroke patients, resulted in lower mortality and improved mice welfare. Finally, a battery of tests covering relevant fine motor skills, sensory functions, and learning/memory behaviors revealed a significant effect of tMCAO brain infarction, which parallel patient symptomatology as measured by relevant clinical scales (NIH Stroke Scale (NIHSS) and modified-Rankin Scale (mRS)). Thus, in order to enhance translation into clinical practice, future preclinical stroke research must consider the methodology described in the present study, including improved reproducible surgical procedure, post-operative care and the battery of functional tests, This will be a major step towards closing the gap from bench to bedside, rendering the development of novel effective therapeutic approaches.